Environmental ethics as a responsible strategy for organizations - Joya Cárdenas, David Eduardo
Currently there have been various changes in areas that form the context of an organization. At same time how to manage processes from different fields, they have had to align with the needs of each company. In this way, the environmental variable is a fundamental factor in the business model today. The purpose of this research is to analyze the different perspectives of environmental ethics as a strategic alternative for the friendly management of organizations with their environment. The development of this, was based on a documentary descriptive research through literature review of articles related to the topic. Regarding the results, the value of ethics and environmental responsibility in proactively managing seeking to develop different organizations focused on environmental management result of self regulation and not by pressure from the various control entities reflected in search of increased levels of competitiveness and improving the corporate image ofcompanies.